Управление многофазным импульсным преобразователем постоянного напряжения с гранично-разрывным режимом функционирования - Gunchenko, Yu. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Regulation characteristics of power channels of buck, boost, and buck–boost types operating in boundary-discontinuous conduction mode are constructed and analyzed. The requirements for the synchronization and control system of a multiphase pulse converter are determined. A synchronization and control system is proposed and described, which ensures a uniform phase shift of electrical processes in the converter with guaranteed avoidance of continuous conduction mode.